Analisis Likuiditas Saham dan Abnormal Return Sebelum dan Sesudah Stock Split Pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Periode 2016-2020 - Arie Budi Santoso; Niko Silitonga (SAFE-Network, 2023)
This study aims to analyze the differences in stock liquidity before and after the stock split and to analyze the differences in abnormal returns before and after the stock split in companies listed on the Indonesia Stock Exchange for the 2016-2020 period. Sampling of 43 companies using purposive sampling technique. Hypothesis testing uses the Paired Sample T Test for data that is normally distributed and the Wilcoxon Rank Test for data that is not normally distributed. The results of the study concluded that there were no differences in stock liquidity before and after the stock split and there were differences in abnormal returns before and after the stock split.